PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENADAHAN BENDA YANG MENJADI OBJEK JAMINAN FIDUSIA (Studi Putusan Mahkamah Konstitusi RI Nomor 18/PUU-XVII/2019) - Suryan (2021)
This study aims to identify and explain about criminal regulation for criminal offenders who transfer fiduciary security based on the provisions of the applicable laws. And to find out and explain about law enforcement efforts against the perpetrator of detention of objects that become fiduciary guarantees. The theory used is the theory of rule of law, theory of law enforcement, and the theory of crime and punishment. The research method used is a juridical analysis method with a qualitative approach. The results of the research, the issuance of the Decision of the Constitutional Court of the Republic of Indonesia Number 18 / PUU-XVII / 2019 on January 6, 2020 had a significant impact on legal issues on fiduciary guarantees, particularly on the provisions of Article 15 of the Fiduciary Guarantee Law which in essence is the fiduciary guarantee certificate. , does not necessarily have executorial power like a court decision having permanent legal force, but it must be interpreted who is found to have committed a breach of contract, and if the debtor does not voluntarily hand over the object of fiduciary collateral due to inability to make payment obligations to the creditor, then the civil court route will be able to determine who is declared in default, but if the fiduciary security object turns out to have been transferred, traded, leased or pawned to a third party or collector, then it can be ascertained that the debtor cannot submit the object of the fiduciary guarantee to the creditor effectively. karela, and how to ensnare the law on fiduciary parties whose object is a fiduciary security object, while juridically normative in the special provisions of the Fiduciary Guarantee Law and in legal consideration of the Constitutional Court Decision Number 18 / PUU-XVII / 2019 there is no single provision that regulates the fiduciary or detention, so that in this research the legal opinion is that there is a need for a revision in the Fiduciary Guarantee Law to contain provisions on detention. Conclusion, The basis for the criminal charges filed against the debtor in terms of transferring or transferring, pawning, renting the object of fiduciary security that has been registered with the fiduciary guarantee agency is Article 36 of Law Number 42 of 1999 concerning Fiduciary Security and if the object of fiduciary security is not registered with The Fiduciary Guarantee Institution is a general crime as regulated in the 372 Criminal Code. Law enforcement for the detention of fiduciary collateral objects cannot be convicted, with the exception of the object of detention originating from embezzlement of Article 372 of the Criminal Code whose fiduciary guarantee is not registered with the Fiduciary Guarantee Institution based on Article 480 of the Criminal Code and in the Constitutional Court Decision only focuses on the Judicial Review of the execution of the fiduciary guarantee object.